Controle de acesso a serviços usando Smart Contracts - Souza, Marcos Vinicius M. R.; Guardia, Helio C. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2019: Anais do II Workshop em Blockchain: Teoria, Tecnologia e AplicaçõesDO - 10.5753/wblockchain.2019.7486, 2019)
Advances in ubiquitous computing and in the Internet of things (IoT) bring new challenges to access control systems, such as not having to rely on a centralized trusted party, and the ability to use contextual data. Such characteristics may be required to enable IoT services in smart homes and cities, and in electronic health systems. In these environments, service-based device to device interactions reinforce the need for flexible and scalable authenticity and confidentiality mechanisms. This work presents an access control model to address such challenges using a blockchain infrastructure. In the proposed model, services and contextual data are defined using smart contracts, and blockchain logs are used for reliable information management. Assets are associated with permissions, and their transfers prove access control rights in service invocation requests. A reference implementation on Hyperledger shows the viability of the model.